(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
This study aimed to identify the role of using the ESG sustainability indicators in enhancing the quality of reporting in economic units, what are the determinants that hinder ESG reporting, and what are the effects of ESG reporting. The deductive approach was used to clarify the triple concept of sustainability, as well as the quality of reporting and the use of the inductive approach in the exploratory study was formulated to verify the research hypotheses with two axes. The first axis measures the effects of the quality of triple sustainability reporting, and the other axis is about the determinants of the quality of triple sustainability reporting. A survey was conducted from the research sample and it was concluded that triple sustainability reporting has a good impact on the markets and is Among the news that the markets interact with, as for the determinants, it was found that there is a legislative and regulatory deficiency in the Iraqi environment for reporting on ESG.